2012
DOI: 10.1590/s0102-09352012000400026
|View full text |Cite
|
Sign up to set email alerts
|

Mapeamento de QTL nos cromossomos 1, 2, 3, 12, 14, 15 e X em suínos: características de carcaça e qualidade de carne

Abstract:  RESUMOA realização do presente estudo teve como objetivo mapear Quantitative Trait Loci (QTL) de carcaça e qualidade de carne em uma população F2 de suínos desenvolvida pelo cruzamento de dois reprodutores da raça brasileira Piau com 18 fêmeas comerciais (Landrace x Large White x Pietrain). O mapa de ligação para essa população foi construído após a genotipagem de 684 animais para 35 marcadores microssatélites. Os dados foram analisados pelo mapeamento por intervalo usando-se sexo, lote e genótipo halotano c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Eight of these had not been reported in the consulted literature: SF and LUNG on SSC4; SBF, PBF and LRBF on SSC8; BW on SSC17; SIL and BCW on SSCX (PigQTLdb). Compared to previous studies that used the same F2 population and relied only on microsatellite markers ( Paixão et al , 2008 , 2012 , 2013 ; Silva et al , 2008 ; Sousa et al , 2011 ), only seven of 40 QTL were confirmed in the present analysis. For these confirmed QTL the confidence intervals were narrowed down on average by 23.9 cM using the dataset with increased marker coverage.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Eight of these had not been reported in the consulted literature: SF and LUNG on SSC4; SBF, PBF and LRBF on SSC8; BW on SSC17; SIL and BCW on SSCX (PigQTLdb). Compared to previous studies that used the same F2 population and relied only on microsatellite markers ( Paixão et al , 2008 , 2012 , 2013 ; Silva et al , 2008 ; Sousa et al , 2011 ), only seven of 40 QTL were confirmed in the present analysis. For these confirmed QTL the confidence intervals were narrowed down on average by 23.9 cM using the dataset with increased marker coverage.…”
Section: Discussioncontrasting
confidence: 87%
“…On SSCX a QTL associated with meat color, A, identified by Paixão et al (2012) was confirmed. The peak of the QTL remained located between markers SW1943 and S0218.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Figure 1 shows that the best methodology was BLASSO, and that the second factor, "fat", showed the most accurate value (0.56) of all four factors. Given the higher accuracy, and its practical relevance for the pig industry (Silva et al, 2011;Paixão et al, 2012;Azevedo et al, 2013aAzevedo et al, , 2015, only the second factor ("fat") will be discussed. The results for the other factors showed the same pattern, and are available at http:// www.det.ufv.br/~moyses/links.php.…”
Section: Resultsmentioning
confidence: 99%